2021
DOI: 10.1136/gutjnl-2021-325574
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic performance of the ‘DICA’ endoscopic classification and the ‘CODA’ score in predicting clinical outcomes of diverticular disease: an international, multicentre, prospective cohort study

Abstract: ObjectiveTo investigate the predictive value of the Diverticular Inflammation and Complication Assessment (DICA) classification and to develop and validate a combined endoscopic-clinical score predicting clinical outcomes of diverticulosis, named Combined Overview on Diverticular Assessment (CODA).DesignA multicentre, prospective, international cohort study.Setting43 gastroenterology and endoscopy centres located in Europe and South America.Participants2215 patients (2198 completing the study) at the first dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The DICA score can predict the outcomes of the disease in terms of AD occurrence/recurrence and surgery. Indeed, after the first promising results coming from a retrospective study [ 43 ], a recent large (more than 2000 patients enrolled) prospective study confirmed that DICA classification plays a significant role in predicting the outcome of the disease since the severity of the DICA score was strictly linked to the risk of having an AD occurrence/recurrence, or to a surgical procedure due to DD complications [ 44 ]. Moreover, the authors found that the clinical evolution of the DICA classification, the CODA (Combined Overview on Diverticular Assessment), combines the DICA score with two clinical parameters; namely, age at baseline and severity of abdominal pain at baseline, showed a more substantial 3-year cumulative probability of diverticulitis and surgery [ 44 ].…”
Section: A New Role For the Colonoscopy In Diverticular Disease: A Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The DICA score can predict the outcomes of the disease in terms of AD occurrence/recurrence and surgery. Indeed, after the first promising results coming from a retrospective study [ 43 ], a recent large (more than 2000 patients enrolled) prospective study confirmed that DICA classification plays a significant role in predicting the outcome of the disease since the severity of the DICA score was strictly linked to the risk of having an AD occurrence/recurrence, or to a surgical procedure due to DD complications [ 44 ]. Moreover, the authors found that the clinical evolution of the DICA classification, the CODA (Combined Overview on Diverticular Assessment), combines the DICA score with two clinical parameters; namely, age at baseline and severity of abdominal pain at baseline, showed a more substantial 3-year cumulative probability of diverticulitis and surgery [ 44 ].…”
Section: A New Role For the Colonoscopy In Diverticular Disease: A Pr...mentioning
confidence: 99%
“…Indeed, after the first promising results coming from a retrospective study [ 43 ], a recent large (more than 2000 patients enrolled) prospective study confirmed that DICA classification plays a significant role in predicting the outcome of the disease since the severity of the DICA score was strictly linked to the risk of having an AD occurrence/recurrence, or to a surgical procedure due to DD complications [ 44 ]. Moreover, the authors found that the clinical evolution of the DICA classification, the CODA (Combined Overview on Diverticular Assessment), combines the DICA score with two clinical parameters; namely, age at baseline and severity of abdominal pain at baseline, showed a more substantial 3-year cumulative probability of diverticulitis and surgery [ 44 ]. These results, together with an extensive validation process performed by experts [ 45 , 46 ] and in real life [ 47 ], confirm that DICA classification may significantly impact the therapeutic choice, and its development opens the way to further, more personalized therapeutic trials in these patients.…”
Section: A New Role For the Colonoscopy In Diverticular Disease: A Pr...mentioning
confidence: 99%
“…Similarly, surgeons cannot predict which patients with acute diverticulitis will go on to suffer severe or recurrent disease. Clinical, radiologic, and endoscopic risk prediction tools have previously been proposed and prospectively studied [13][14][15][16] but have not been effectively adopted into clinical guidelines or common use. As a result of this lack of risk stratification, some patients with diverticulitis are overtreated with unnecessary surgery and others are undertreated, suffering recurrent episodes before a therapeutic operation.…”
mentioning
confidence: 99%
“…The relatively rigid dictum/dogma that used to facilitate operative decision-making by essentially obviating the need to deviate from the algorithm has been replaced by a void as individual management may not always be evidence-based. Therefore, the work by Tursi and colleagues11 is indeed important in helping us to fill this void by potentially giving us some direction as to who with diverticular disease might need surgery. This very modern approach would be a welcome replacement to the now no longer practised age and number of episode-based criteria.…”
mentioning
confidence: 99%
“…Tursi and coworkers11 are to be commended for having amassed 2198 patients who completed the study in 43 gastroenterology and endoscopy enters in Europe and South America. The diverticular inflammation and complication assessment (DICA) classification and the combined overview on diverticular assessment (CODA) are exceptionally intriguing.…”
mentioning
confidence: 99%